2023
DOI: 10.3390/ijms24065965
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Malat1 Increases the Rescuing Effect of Quercetin on TNFα-Impaired Bone Marrow Stem Cell Osteogenesis and Ovariectomy-Induced Osteoporosis

Abstract: Osteoporosis, a common systematic bone homeostasis disorder related disease, still urgently needs innovative treatment methods. Several natural small molecules were found to be effective therapeutics in osteoporosis. In the present study, quercetin was screened out from a library of natural small molecular compounds by a dual luciferase reporter system. Quercetin was found to upregulate Wnt/β-catenin while inhibiting NF-κB signaling activities, and thereby rescuing osteoporosis-induced tumor necrosis factor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[ 37 ] Studies have shown that reducing the expression of TNF-α can increase the bone mineral density of OVX mice and promote the osteogenic differentiation of bone marrow mesenchymal stem cells. [ 38 ] CASP-3 is a crucial molecule involved in the degradation stage of apoptosis and is a promising target for treating OP. Liu et al discovered that increasing the expression of CASP-3 reduced apoptosis of osteoblasts in mice and lowered the expression of osteogenic indicators such as ALP, P1NP, and osteocalcin.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Studies have shown that reducing the expression of TNF-α can increase the bone mineral density of OVX mice and promote the osteogenic differentiation of bone marrow mesenchymal stem cells. [ 38 ] CASP-3 is a crucial molecule involved in the degradation stage of apoptosis and is a promising target for treating OP. Liu et al discovered that increasing the expression of CASP-3 reduced apoptosis of osteoblasts in mice and lowered the expression of osteogenic indicators such as ALP, P1NP, and osteocalcin.…”
Section: Discussionmentioning
confidence: 99%